30-40 Beurs jonge kunst Knokke. - De Nys, Jan; Lambrecht, Luk; Vroonen, Erno (Knokke : Cultureel Centrum Scharpoord, 1995)
Andora ; Balis, Al ; Baudart, Johan ; Bechinger, Thomas ; Berlanger, Marcel ; Biwer, Jean-Marie ; De Blieck, Marc ; Blokland, Wido ; Bonhansa ; de Boo, Stella ; Bos, Karin ; Bosman, Ria ; Boyen, Diederik ; Brahe, Henrik ; Broucke, Koen ; Calle, Sophie ; Caminiti, Martin ; van Campenhout, Ad ; Cattaneo, Stefano ; Ceulemans, Els ; Clas, Maja ; Combas, Robert ; Cops, Pierre ; Creimer, Georgia ; Daems, Anne ; Dehais, Dominique ; Desmedt, Emile ; diepens, carina ; van Eeden, Marcel ; Engels, Waldo ; Farb, Adrienne ; Feiereisen, Marie-Paule ; Feldman, Kathryn ; Fischer, Roland ; Garnett, Christian ; Gerlach, Diederik ; Gorter, Bart ; De Groote, Jean ; Ham, Hans Van Der ; van Ham, Milou ; Hartjesveld, Elsa ; Heyman, Frederik ; Hortala, Philippe ; Jacobs, Carl ; Kalfas, Christos ; Kantor, Zvika ; Kienzer, Michael ; Kleinlein, Gisela ; Klenes, Anne-Marie ; Kortschot, Arno ; Kuitenbrouwer, Mirjam ; Langhoff, Silvia ; Larrivaz, Dominique ; Lemmen, Hans ; Lindemann, Sabrina ; Van Lith, Lex ; Lomré, Dominique ; Murawa, Tonn Prins ; Musa, Muriël ; van Oel, Martin ; van Ojen, Vincent ; Palma, Luis Gonzalez ; Panier, Claude ; Pfeifer, Stefan ; Pierret, Marc ; Ploegaert, William ; Pries, Inge ; Reeder, Dan ; Reiterer, Werner ; Rodenberg, Ellen ; Roorda, Anne R. ; Rousselot, Bruno ; Sagna, William ; Schoutsen, Peter ; Simon, Walter ; Smith, Alan ; Stuer, Maarten ; Thorsteinsson, Thorvaldur ; Tooke, Robert ; Touron, Jérôme ; Ulmer, Bruno ; Urbain, Thierry ; Vandekerkhove, Karien ; Vanderheijden, Michel ; Vandevijvere, Bart ; Vanneste, Karel ; Verf, Rob ; van der Vleuten, Ans ; Vos, Rob ; van Vught, Reinoud ; Welzenbach, Andreas ; van der Werff, Lie ; Wijns, Geert ; Wiltshire, Hermione ; Wittevrongel, Erwin ; Zalme, Marcel ; zhao, Yongbo ; Zijlstra, Roeland ; van Zoelen, Paul ; etc.
30-40 Beurs jonge kunst Knokke, Cultureel Centrum Scharpoord, Knokke-Heist, 14-23 juli 1995
Nederlands & Frans & Duits & Engels
kunstcatalogus